Echocardiographic assessment of left ventricular midwall mechanics in spontaneously hypertensive rats - Escudero, Eduardo Manuel (2004)
Aims. The present study was attempted to determine whether LV midwall mechanics yielded different conclusions about LV systolic function than the assessment of endocardial LV mechanics by echocardiography in spontaneously hypertensive rats (SHR). Methods and results. Thirty-six (18 Wistar normotensive (W), 18 [SHR]) anesthetized rats were studied with two-dimensional directed M-mode echocardiogram to analyze LV structure (LV diameter, left ventricular wall thickness and LV mass [LVM]) and LV function (endocardial shortening [ES] and midwall shortening [MS]). Measurements were made from three consecutive cardiac cycles on the M-mode tracings. There was no significant difference in LV dimension. LVM was higher in SHR (SHR: 595 ± 111 mg, W: 413 ± 83 mg - p < 0.01). ES was higher in SHR (SHR: 64.1 ± 6%, w: 58.2 ± 4% - p < 0.01), whereas no significant difference was found in MS (SHR: 27 ± 4%, W: 27.6 ± 4% - ns). Twelve of 18 (66%) SHR showed endocardial shortening higher than normally predicted, compared with 3/18 (16%) with observed enhanced MS (p < 0.01). Conclusion. These results suggest that the analysis of midwall mechanics by echo allows us to better understand the LV performance in SHR and that the exaggerated endocardial motion could not represent a really supernormal systolic performance.